Postoperative complications and hernia recurrence after the use of various ventral hernia repair techniques - Ioffe, O. Y.; Tarasiuk, T. V.; Kryvopustov, M. S.; Stetsenko, O. P. (General Surgery, 2024)
Prosthetic hernioplasty (HP) for ventral hernias (VH) has a complication rate of up to 27% and a hernia recurrence rate up of to 37%, depending on the chosen technique. The use of laparoscopic HP techniques allows for a shorter hospital stay and a lower risk of wound infection. There is a wide range of data on the superiority of laparoscopy over the open technique in terms of recurrence rates and various types of complications. The results of comparing HP with and without suturing of the hernia defect are controversial. Objective — to study the structure and incidence of postoperative complications, as well as the frequency of hernia recurrences after the use of open and laparoscopic HP for VH. Materials and methods. A multicenter prospective study, which included 482 patients diagnosed with VH, was conducted at the clinical base of the Department of General Surgery No. 2 at Bogomolets National Medical University. A total of 279 (57.9%) patients had primary VH, while 203 (42.1%) had incisional VH. The patients were divided into two groups, comparable in terms of age, sex, and hernia size distribution. Group 1 included 250 (51.9%) patients who underwent open HP with suturing of the hernia defect: subgroup 1a — open sublay (n=243; 50.4%), and subgroup 1b — open intraperitoneal onlay mesh technique (IPOM) (n=7; 1.5%). Group 2 included 232 (48.1%) patients who underwent laparoscopic HP using the IPOM technique: subgroup 2a — IPOM without suturing of the aponeurosis defect (n=81; 16.8%), subgroup 2b — IPOM with suturing of the aponeurosis defect (n=108; 22.4%), and subgroup 2c — IPOM+ with open aponeurosis defect suturing (n=43; 8.9%). Follow‑up evaluations were carried out at intervals of 2 weeks, 1 month, 6 months, and 1 year to assess the presence of complications, recurrence, and satisfaction with the cosmetic effect of the operation. Results. The overall frequency of complications after HP was 15.6%, while after open sublay it was 21.2%, and after laparoscopic IPOM it was 9.9%. All cases of complications belonged to Grades I—IIIb according to the Clavien‑Dindo classification. In both groups, there were no fatalities. In group 1, the frequency of seroma was 11.6% and hematoma was 5.6%, and in group 2, it was 7.3% and 0.9%, respectively. A statistically significant increase in the frequency of hematoma development was observed after open HP techniques compared to laparoscopic ones (p=0.004), while the frequency of seroma detection was comparable (p=0.148). Non‑suturing of the aponeurosis defect after laparoscopic IPOM in patients with VH did not result in an increase in the total number of complications or the percentage of recurrence (p >0.05). Laparoscopic IPOM with hernia suturing demonstrated significantly higher patient satisfaction with the appearance of the anterior abdominal wall compared to other HP techniques (р <0.05). Conclusions. The open sublay and laparoscopic IPOM HP procedures have a comparable recurrence rate of VH (p >0.05). The incidence of infectious complications and hematomas is significantly higher after open operations compared to laparoscopic ones (p=0.041 and p=0.004, respectively).